INOVASI PEMBELAJARAN MENGGUNAKAN HYBRID CURRICULUM DI AQOBAH INTERNASIONAL SCHOOL JOMBANG - TIFTAZANI, SYAZA; PURWOKO, BUDI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Learning innovation in education is currently the main key in preparing a competent generation that is ready to face global challenges. One of the growing innovations is the implementation of hybrid curriculum, which is a combination of various types of curriculum to create a more holistic learning experience. This article discusses the implementation of a hybrid curriculum that combines the national curriculum, pesantren curriculum, and cambridge curriculum at Aqobah International School Jombang. The purpose of this study is to explore how this hybrid learning model is implemented, as well as to evaluate its impact on the quality of learning and student learning outcomes and to be a strategic step in facing the challenges of modern education. This learning model is designed to create a more interactive and student-centred learning experience, where they are encouraged to actively participate in the learning process. Students not only gain academic knowledge, but also delve into the spiritual aspect through the Qur'an tahfidz programme and yellow book studies. In this curriculum, students are targeted to memorise 5 juz of the Qur'an during the three years of education, as well as learn the science of nahwu and shorof. In addition, Aqobah International School also provides specialisation programmes that allow students to develop specific skills according to their interests. These programmes cover various fields such as leadership, technology, and diplomacy. With this approach, the school not only focuses on academic outcomes, but also on developing students' character and social skills. Through this innovation, Aqobah International School is committed to creating a generation that is not only academically smart but also has integrity and strong moral values. The hybrid curriculum is expected to be a relevant and effective education model in preparing students to face global challenges in the future. ABSTRAK Inovasi pembelajaran di dunia pendidikan saat ini menjadi kunci utama dalam mempersiapkan generasi yang kompeten dan siap menghadapi tantangan global. Salah satu inovasi yang berkembang adalah penerapan hybrid curriculum, yaitu penggabungan berbagai jenis kurikulum untuk menciptakan pengalaman belajar yang lebih holistik. Artikel ini membahas penerapan hybrid curriculum yang menggabungkan kurikulum nasional, kurikulum pesantren, dan kurikulum cambridge di Aqobah Internasional School Jombang. Tujuan dari penelitian ini adalah untuk mengeksplorasi bagaimana model pembelajaran hibrid ini diterapkan, serta untuk mengevaluasi dampaknya terhadap kualitas pembelajaran dan hasil belajar siswa dan menjadi langkah strategis dalam menghadapi tantangan pendidikan modern. Model pembelajaran ini dirancang untuk menciptakan pengalaman belajar yang lebih interaktif dan berpusat pada siswa, di mana mereka didorong untuk aktif berpartisipasi dalam proses pembelajaran. Siswa tidak hanya mendapatkan pengetahuan akademis, tetapi juga mendalami aspek spiritual melalui program tahfidz Al-Qur'an dan kajian kitab kuning. Dalam kurikulum ini, siswa ditargetkan untuk menghafal 5 juz Al-Qur'an selama tiga tahun pendidikan, serta mempelajari ilmu nahwu dan shorof. Selain itu, Aqobah Internasional School juga menyediakan program spesialisasi yang memungkinkan siswa untuk mengembangkan keterampilan khusus sesuai minat mereka. Program ini mencakup berbagai bidang seperti kepemimpinan, teknologi, dan diplomasi. Dengan pendekatan ini, sekolah tidak hanya fokus pada hasil akademis, tetapi juga pada pengembangan karakter dan keterampilan sosial siswa. Melalui inovasi ini, Aqobah Internasional School berkomitmen untuk menciptakan generasi yang tidak hanya cerdas secara akademis tetapi juga memiliki integritas dan nilai-nilai moral yang kuat. hybrid curriculum diharapkan dapat menjadi model pendidikan yang relevan dan efektif dalam mempersiapkan siswa menghadapi tantangan global di masa depan.